PELATIHAN APLIKASI CANVA PADA GURU P A U D TUNAS BANGSA UNTUK MENINGKATKAN KREATIFITAS PEMBELAJARAN - Supriyanto, Aji; Hadiono, Kristophorus; Widyaningrum, Agnes; Damaryanti, Rr Fitri (Intimas, 2024)
Early Childhood Education (PAUD) is education that is very important in giving birth to a golden generation in Indonesia. The Canva application can be used for digital-based learning for PAUD because it is easy, complete, interesting, creative and innovative, and can be done online. However, there are still many PAUD teachers who have not mastered its use in learning materials. Canva training for PAUD learning aims to improve teachers' abilities in mastering the Canva application in digital learning in PAUD to make it more creative and innovative but easy and fun. PAUD Teacher Training is carried out by trying directly on a laptop with the online Canva application available by trying out various available features with adapting the material for PAUD. PAUD teachers try it on their respective laptops that are connected to the internet and are accompanied by instructor assistants to make learning activities easier and smoother. Examples are provided directly for PAUD teachers to practice to make it easier to understand the online Canva learning material. As a result, PAUD teachers can practice digital learning with Canva using dynamic, creative, innovative and interesting features for PAUD.